2022
DOI: 10.3390/agronomy12071710
|View full text |Cite
|
Sign up to set email alerts
|

SNP Genotyping for Purity Assessment of a Forage Oat (Avena sativa L.) Variety from Colombia

Abstract: Single nucleotide polymorphism (SNP) markers have multiple applications in plant breeding of small grains. They are used for the selection of divergent parents, the identification of genetic variants and marker-assisted selection. However, the use of SNPs in varietal purity assessment is under-reported, especially for multi-line varieties from the public sector. In the case of variety evaluation, these genetic markers are tools for maintaining varietal distinctness, uniformity and stability needed for cultivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Genomics is speeding up multiple steps in the breeding scheme (Table 1). For instance, in the downstream extreme of the breeding pipeline, Campuzano-Duque et al [12] demonstrated the utility of high-throughput single nucleotide polymorphism (SNP) genotyping using SNP arrays to trace varietal purity of single plant selections (SPS). The authors successfully assessed the relationships and ancestry of plant selections from three inbreed origins (one original variety and two additional multi-lines) of forage oat (Avena sativa), and prioritized SNP candidates to ensure the genetic purity of these varieties.…”
Section: Genomic-enabled Crop Traceability and Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomics is speeding up multiple steps in the breeding scheme (Table 1). For instance, in the downstream extreme of the breeding pipeline, Campuzano-Duque et al [12] demonstrated the utility of high-throughput single nucleotide polymorphism (SNP) genotyping using SNP arrays to trace varietal purity of single plant selections (SPS). The authors successfully assessed the relationships and ancestry of plant selections from three inbreed origins (one original variety and two additional multi-lines) of forage oat (Avena sativa), and prioritized SNP candidates to ensure the genetic purity of these varieties.…”
Section: Genomic-enabled Crop Traceability and Improvementmentioning
confidence: 99%
“…Data Availability Statement: Raw datasets were made available by each of the ten published articles [11][12][13][14][15][16][17][18][19][20] from the Special Issue on "Omics Approaches for Crop Improvement" (https://www. mdpi.com/journal/agronomy/special_issues/crop_omics_genetic (revised 18 May 2023).…”
mentioning
confidence: 99%